Commercial Gold(I) and Gold(III) Compounds Supported on Carbon Materials as Greener Catalysts for the Oxidation of Alkanes and Alcohols. Issue 8 (24th April 2018) - Carabineiro, Sónia A. C.; Martins, Luísa M. D. R. S.; Pombeiro, Armando J. L.; Figueiredo, José L.
Abstract: The front cover artwork for issue 8/2018 stems from a collaboration between the Universities of Porto and Lisbon (Portugal). The image shows two reactions of industrial importance, namely the oxidation of cyclohexane and the oxidation of methyl benzyl alcohol, catalyzed by commercial gold complexes anchored on functionalized carbon nanotubes, in "greener conditions". See the Full Paper itself at https://doi.org/10.1002/cctc.201701886 . Abstract : "Efficient single‐pot oxidative functionalization of cyclohexane and alcohols, under mild conditions, was catalyzed by Au I or Au III complexes supported on activated carbon, carbon xerogel, and multi‐walled carbon nanotubes." This and more about the story behind the research featured on the front cover can be found in this issue's Cover Profile. Read the full text of the corresponding research athttps://doi.org/10.1002/cctc.201701886 .